1994
DOI: 10.1021/bi00178a031
|View full text |Cite
|
Sign up to set email alerts
|

Calcium-Binding Properties of a Calcium-Dependent Protein Kinase from Plasmodium falciparum and the Significance of Individual Calcium-Binding Sites for Kinase Activation

Abstract: Calcium-dependent protein kinase from Plasmodium falciparum (PfCPK) is a multidomain protein composed of an N-terminal kinase domain connected via a linker region to a C-terminal CaM-like calcium-binding domain. The kinase can be activated by Ca2+ alone and associates with 45Ca2+. Here we describe the calcium-binding properties of the kinase and the significance of the individual calcium-binding sites with respect to enzymatic activation, as well as the Ca(2+)-induced conformational change as detected by circu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
45
1

Year Published

1995
1995
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(54 citation statements)
references
References 46 publications
8
45
1
Order By: Relevance
“…This value was lower than previously reported values for soybean (Glycine max) CDPK-b (K 0.5 5 0.4 mM) and CDPK-g (K 0.5 5 1.0 mM), with only CDPK-a (K 0.5 5 0.06 mM), measured in the presence of the peptide substrate syntide-2, having a lower value . This value was also higher than that obtained for sandalwood (Santalum album) CDPK (0.7 mM) with histone III-S as a substrate (Anil and Rao, 2001); however, it was lower than the K 0.5 for histone III-S phosphorylation (about 4 mM) by soybean CDPK-a or for casein phosphorylation by Plasmodium falciparum CDPK1 (Zhao et al, 1994).…”
Section: Biochemical Characterization Of Mccpk1mentioning
confidence: 45%
See 1 more Smart Citation
“…This value was lower than previously reported values for soybean (Glycine max) CDPK-b (K 0.5 5 0.4 mM) and CDPK-g (K 0.5 5 1.0 mM), with only CDPK-a (K 0.5 5 0.06 mM), measured in the presence of the peptide substrate syntide-2, having a lower value . This value was also higher than that obtained for sandalwood (Santalum album) CDPK (0.7 mM) with histone III-S as a substrate (Anil and Rao, 2001); however, it was lower than the K 0.5 for histone III-S phosphorylation (about 4 mM) by soybean CDPK-a or for casein phosphorylation by Plasmodium falciparum CDPK1 (Zhao et al, 1994).…”
Section: Biochemical Characterization Of Mccpk1mentioning
confidence: 45%
“…Various signals modulate intracellular Ca 21 levels (Rudd and Franklin-Tong, 2001;Sanders et al, 2002 Zhao et al (1994) showed that only the first EF hand of PfCPK1 needed to be functional in order to undergo Ca 21 activation. Rutschmann et al (2002) …”
Section: Biochemical Characterization Of Mccpk1mentioning
confidence: 99%
“…Experimental evidence indicates a differential contribution of N-terminal and C-terminal EF lobes within the CAD in either stabilizing or releasing the pseudosubstrate region (Christodoulou et al, 2004). Furthermore, CDPK variants, harboring site-specific amino acid substitutions in single or double EF hand motifs, demonstrated a differential requirement of the N-and C-terminal EF hand pairs in standard in vitro protein kinase assays (Zhao et al, 1994;Franz et al, 2011). Remarkably, a comparison between Ca 2+ binding and phosphorylation activity identified Arabidopsis CDPKs that displayed apparent Ca 2+ -insensitive kinase activity.…”
Section: The Cdpk Activation Domain: Are All Cdpks Regulated By Calcimentioning
confidence: 99%
“…Sequential deletion of the EF hands demonstrates that the number of EF hands may be important for determining calcium regulation of CDPK activity (Hong et al, 1996). In addition, site-directed mutagenesis of a highly conserved Glu residue in each EF hand shows that the closer the EF hand is to the autoinhibitory domain, the greater its effect on the Ca 2ϩ regulation of CDPK activity (Zhao et al, 1994). The mechanism by which CDPK activity is regulated is largely controlled through interactions between the kinase, autoinhibitory, and calmodulinlike domains.…”
Section: Domain Structurementioning
confidence: 99%